Pre-alerts from critical care ambulances to trauma centers: a quantitative survey of trauma team leaders in Ontario, Canada - Tara Williams; Brodie Nolan; Melissa McGowan; Tania Johnston; Sonja Maria; Johannes von Vopelius-Feldt (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2024)
Abstract Introduction Pre-alerts from paramedics to trauma centers are important for ensuring the highest quality of trauma care. Despite this, there is a paucity of data to support best practices in trauma pre-alert notifications. Within the trauma system of Ontario, Canada, the provincial critical care transport organization, Ornge, provides pre-alerts to major trauma centers, but standardization is currently lacking. This study examined the satisfaction of trauma team leaders’ (TTLs) satisfaction with current trauma pre-alerts and their preferences for logistics, content, and structure. Methods This was a quantitative survey of TTLs at adult and pediatric trauma centers across Ontario, Canada. Recruitment was through email to trauma directors, with follow-up efforts to target low-response sites to achieve good geographical representation. The survey was completed online and contained a combination of single or multiple-choice questions, Likert scales and free text options. Results In total, 79 TTLs from adult and pediatric lead trauma centers across Ontario responded to the survey, which took place over a 120-day period. The survey achieved good geographical representation. Given the current processes, TTLs describe moderate satisfaction with room for improvement (median score 3, IQR 3–4 on a 5-point Likert scale). Their overall preference was for timely and direct communication, with some concerns about multiple channels of communication around logistics. Most TTLs agreed on the important and less important content details found in common standardized framework tools. For structure, 28/79 TTLs strongly preferred the cognitive aid ATMIST, 13/79 preferred IMIST-AMBO, and 8/79 preferred MIST or SBAR as the most useful. Conclusions There is room for improvement through standardizing communication and streamlined pre-alert channels. Some disagreements exist between TTLs, particularly regarding logistics. Further research should examine TTL satisfaction after implementing the change in the pre-alert notification framework, which can address localized issues through stakeholder meetings with individual TTLs.